Implikasi Penerapan Asimilasi Rumah Bagi Narapidana Pada Masa Pandemi Covid-19 Dari Perspektif Tujuan Pemidanaan di Indonesia - Mataheru, Hendarina; Titahelu, Juanrico Alfaromona Sumarezs; Lewerissa, Yanti Amelia (PAMALI: Pattimura Magister Law Review, 2024)
Introduction: Suppressing the rate of spread of Covid-19 in prisons, several regulations were issued that regulate the provision of home assimilation to prisoners. However, the provision of home assimilation raises pros and cons in society, especially when looking at assimilation from the perspective of the purpose of funding.Purposes of the Research:  The purpose of this study is to examine and analyze the implications of implementing home assimilation for prisoners during the Covid-19 pandemic from the perspective of the purpose of punishment in Indonesia.Methods of the Research: This research is normative juridical research, the research approach used is a statutory approach, a conceptual approach and a case approach. The sources of legal materials used in this study are primary legal materials and secondary legal materials. The technique of collecting legal materials is in the study of literature and subsequently analyzed qualitatively.Results of the Research: The results showed that the provision of home assimilation during the Covid-19 pandemic when viewed from the purpose of punishment, the provision of home assimilation was in accordance with the purpose of punishment. This is because, government policies to reduce the rate of spread of the Covid-19 virus in various public spaces including in prisons through home assimilation programs do not just run. However, it is accompanied by various rules that regulate a number of conditions that must be met by an inmate to be able to participate in home assimilation. Prisoners must behave well during their sentences and follow all coaching programs implemented in Lapas. This means that, inmates who pass the home assimilation program, are those who are judged to have had a better change in attitude and behavior, obey and obey the rules made (especially in Lapas), and ready to blend in with the community. All of them are the purpose of punishment which is not to take revenge for the evil behavior that has been committed by an inmate, but rather to humanize humans (prisoners) through various formation programs implemented in the Penitentiary.